(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: One of the growing epidemics in the world today is HIV/AIDS. In the cities with high mobility, bus drivers and transport workers are considered as the risk group for HIV/AIDS. In Kavre district, the increased mobility along with Araniko highway and Banepa Bardibas highways has drastically increased the vulnerabilities of younger populations in particularly to HIV/AIDS and STDs. Most of these young people do not have access to information, condoms, supportive services which enable them to have safer sex. Methodology: A descriptive cross sectional study was done to assess knowledge about HIV/AIDS among bus drivers of Dhulikhel. Results: After the analysis and interpretation of the data, study revealed that majority of the respondents i.e. 38% (n=19) were between age 20-24 years. Among them vast majority of the respondents i.e 82% (n=41) have heard from media (radio, Television and newspapers). Regarding transmission of HIV/AIDS 90% (n=45) of the respondents mentioned that unsafe sex is the means of transmission. Still 24% (n=12) believe that sharing clothes and 2% (n=1) believe that kissing can transmit HIV/AIDS. As per prevention measures 90% (n=5) have the knowledge that using condom during sexual intercourse can prevent HIV/ AIDS. 8% (n=4) of the respondents still believe that HIV/AIDS is curable and rest of them i.e. 92% (n=46) of the respondents knew that HIV/AIDS is not curable. Conclusion: The present study strongly recommends that there is immediate need of program to create awareness of public motor drivers and co-workers, vulnerable youths and other high risk groups of people including migrant populations. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS 2012; IX (1) 35-38 DOI: http://dx.doi.org/10.3126/saarctb.v9i1.6963